Effects of Ophthalmic Medications on Conjunctival Goblet Cell Density in New Zealand White Rabbits - Sarahi del Carmen Gómez Macías; Ricardo Osvaldo Jauregui Franco; José María Torres-Arellano; Elba Yadira Correa Gallegos; José Manuel Medina Espinosa; Alejandra Sánchez Ríos; Oscar Olvera Montaño (Biomedicine Hub)
Introduction: The conjunctiva contains numerous specialized cells called conjunctival goblet cells (CGCs). The topical application of specific eye drops to the ocular surface has conclusively been linked to cause a reduction in CGCs, a condition which has been associated with dry eye and other ocular surface disorders. The purpose of this study was to assess if the use of benzalkonium chloride (BAK) as a preservative in common ophthalmic medications affects CGCs’ density in New Zealand white (NZW) rabbit conjunctivas. Methods: Data from seven preclinical studies conducted between March 2016 and April 2021 were analyzed, involving 146 male NZW rabbits aged 2 to 3 months. Prior to study participation, rabbits underwent a 7-day quarantine period in individual housing, during which their general health was monitored. Rabbits had ad libitum access to water and food, with intake data recorded. Comprehensive ophthalmological examinations were performed on all eyes prior to and throughout the studies. The density of corneal endothelial cells was specifically assessed using AB/PAS staining and quantified with a high-power (40X) field objective (ocular 18 × 22), expressed as a percentage relative to epithelial cells. Results: No statistically significant differences were found between the with-BAK group and without-BAK group. The mean density in the 30-day group presented a statistically significant higher density than the >30-day group (p = 0.005). Analysis of the treatment revealed that antibiotic/steroid combination group had a higher average number of CGCs compared to both the antihistaminic group (p = 0.004) and hypotensive agent group (p = 0.047). Conclusion: Exposure to BAK-preserved medications for 30 days results in a higher density of CGCs compared to prolonged exposure to BAK-preserved medications exceeding 30 days. The pharmacological effects and associated cellular damage induced by BAK vary depending on the specific medication with which it is combined.